2019
DOI: 10.1002/dta.2580
|View full text |Cite
|
Sign up to set email alerts
|

Beta2‐adrenergic ligand racemic formoterol exhibits enantioselective disposition in blood and skeletal muscle of humans, and elicits myocellular PKA signaling at therapeutic inhaled doses

Abstract: While studies have demonstrated substantial differences in beta2‐adrenergic agonist enantiomer pharmacology, enantioselective disposition of long‐acting beta2‐adrenergic ligand racemic (rac)‐formoterol in blood is inadequately explored after inhaled therapy given analytical challenges. Furthermore, information on enantioselective disposition and partitioning of beta2‐adrenergic agonist in skeletal muscle is absent despite its promising data on muscle anabolism in humans. Using a sensitive ultra‐high performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…We observed that clenbuterol effectively induced PKA and mTOR phosphorylation in skeletal muscle. Given that the PKA‐dependent signaling pathway is the canonical signaling pathway associated with the beta 2 ‐adrenoceptor, the observed increase in PKA substrate phosphorylation with clenbuterol was expected and was consistent with that observed for formoterol and salbutamol in human skeletal muscle . The increase of 121% in mTOR Ser2448 phosphorylation, however, was larger than expected, and may indicate anabolic signaling in the absence of exercise.…”
Section: Discussionsupporting
confidence: 81%
“…We observed that clenbuterol effectively induced PKA and mTOR phosphorylation in skeletal muscle. Given that the PKA‐dependent signaling pathway is the canonical signaling pathway associated with the beta 2 ‐adrenoceptor, the observed increase in PKA substrate phosphorylation with clenbuterol was expected and was consistent with that observed for formoterol and salbutamol in human skeletal muscle . The increase of 121% in mTOR Ser2448 phosphorylation, however, was larger than expected, and may indicate anabolic signaling in the absence of exercise.…”
Section: Discussionsupporting
confidence: 81%
“…−1 × day −1 (Kalinovich et al 2020) would yield a systemic exposure 80 times exceeding that recommended for humans (Maltin et al 1993;Kamalakkannan et al 2008;Koeberl et al 2018). Therefore, we encourage research to be conducted with newer-generation and enantioselective beta 2 -agonists because of their greater selectivity for the beta 2 -adrenergic receptor and fewer cardiac side effects (Jacobson et al 2018;Hostrup et al 2019), and in doses more closely resembling those clinically relevant. Pharmaceutical development of novel beta 2 -agonists that are more specific to skeletal muscle tissue is ongoing (Koziczak-Holbro et al 2019) and could, in combination with exercise, diet or other treatment regimens, prove useful in weight-loss management.…”
Section: Discussionmentioning
confidence: 98%
“…Upon agonist binding to the beta 2 ‐adrenoceptor, various intracellular signalling pathways are activated as shown in Figure . The cAMP/protein kinase A (PKA)‐dependent pathway is the canonical signalling pathway activated upon beta 2 ‐adrenergic stimulation as also shown in human skeletal muscle after treatment with salbutamol and formoterol . The cAMP/PKA‐dependent pathway has several downstream targets that regulate metabolism and gene programs in skeletal muscle fibres.…”
Section: Mechanisms Underlying the Anabolic Actions Of Beta2‐agonistsmentioning
confidence: 97%
“…While muscle hypertrophy is scarcely explored for the inhaled route, daily inhalation of terbutaline at 4 mg (8 puffs from a 0.5 mg Turbohaler) for 4 weeks was recently shown to induce a 1 kg gain in lean mass in healthy young men . In addition, an inhaled dose of 54 μg formoterol (6 puffs from a 9 μg Turbohaler), a dose that lies within the current WADA threshold limit, induces skeletal muscle signalling and increases resting metabolic rate, fat oxidation, and peripheral glucose uptake . The same is the case for salbutamol, which via the inhaled route has been shown to induce lipolysis at therapeutic doses and to increase resting metabolic rate .…”
Section: Inhalation Of Beta2‐agonists At High Doses Exerts Similar Efmentioning
confidence: 99%